Tubulin Sorting during Dimerization In Vivo - Hoyle, Henry D. (The American Society for Cell Biology, 2001)
We demonstrate sorting of β-tubulins during dimerization in the Drosophila male germ line. Different β-tubulin isoforms exhibit distinct affinities for α-tubulin during dimerization. Our data suggest that differences in dimerization properties are important in determining isoform-specific microtubule functions. The differential use of β-tubulin during dimerization reveals structural parameters of the tubulin heterodimer not discernible in the resolved three-dimensional structure. We show that the variable β-tubulin carboxyl terminus, a surface feature in the heterodimer and in microtubules, and which is disordered in the crystallographic structure, is of key importance in forming a stable α-β heterodimer. If the availability of α-tubulin is limiting, α-β dimers preferentially incorporate intact β-tubulins rather than a β-tubulin missing the carboxyl terminus (β2ΔC). When α-tubulin is not limiting, β2ΔC forms stable α-β heterodimers. Once dimers are formed, no further sorting occurs during microtubule assembly: α-β2ΔC dimers are incorporated into axonemes in proportion to their contribution to the total dimer pool. Co-incorporation of β2ΔC and wild-type β2-tubulin results in nonmotile axonemes because of a disruption of the periodicity of nontubulin axonemal elements. Our data show that the β-tubulin carboxyl terminus has two distinct roles: 1) forming the α-β heterodimer, important for all microtubules and 2) providing contacts for nontubulin components required for specific microtubule structures, such as axonemes.